Minimum wages, fringe benefits, and working conditions - Wessels, Walter J. (Washington : American Enterprise Institute for Public Policy Research, 1980)
Minimum wages are widely regarded as having a significant effect on low-wage workers, affecting the value and the stability of their jobs. It examines effect of increases in the minimum wages
Includes bibliographical references.
aia 21/03/2019
Loans
Keywords: Minimum wage; Employee fringe benefits; Hours of labor; Labor supply